A systematic review of prevalence and impact of symptoms of pelvic floor dysfunction in identified workforce groups. (17th February 2016) - Pierce, Heather; Perry, Lin; Chiarelli, Pauline; Gallagher, Robyn
Abstract: Aim: To investigate the prevalence and impact of symptoms of pelvic floor dysfunction in identified workforce groups. Background: Productivity of workforce groups is a concern for ageing societies. Symptoms of pelvic floor dysfunction are associated with ageing and negatively influence psychosocial health. In the general population, lower urinary tract symptoms negatively influence work productivity. Design: A systematic review of observational studies. Data sources: Electronic searches of four academic databases. Reference lists were scanned for relevant articles. The search was limited to English language publications 1990–2014. Review methods: The Centre for Reviews and Dissemination procedure guided the review method. Data extraction and synthesis was conducted on studies where the workforce group was identified and the type of pelvic floor dysfunction defined according to accepted terminology. Quality appraisal of studies was performed using a Joanna Briggs Institute critical appraisal tool. Results: Twelve studies were identified of variable quality, all on female workers. Nurses were the most frequently investigated workforce group and urinary incontinence was the most common subtype of pelvic floor dysfunction examined. Lower urinary tract symptoms were more prevalent in the studied nurses than related general populations. No included study investigated pelvic organ prolapse, anorectal or male symptoms or the influence of symptoms on work productivity. Conclusion: Lower urinary tract symptoms are a significant issue among the female nursing workforce. Knowledge of the influence of symptoms on work productivity remains unknown. Further studies are warranted on the impact of pelvic floor dysfunction subtypes in workforce groups.